Work Effectiveness of Employees in the Gowa Regional Revenue Technical Implementation Unit - Sirajuddin Saleh; Dea Tenri Bau; Muh. Darwis (Asha Publishing, 2024)
Effectiveness is a state that shows the success of the specified work. Work effectiveness is the completion of work on time that has been determined, meaning that the implementation of a task that is well marked or not, depends largely on the completion of the task how to carry it out. This study aims to determine the Work Effectiveness of Employees in the Gowa Regional Revenue Technical Implementation Unit. The data collection techniques used are observation, interviews and documentation. The informants in this study were 5 (five) employees, namely the Administration Department, Tax Analysis, Revenue and Collection Staff, Determination and Revenue Staff, Administration Staff, and 1 (one) service user. The results showed that the effectiveness of employee work in the Gowa Regional Revenue Technical Implementation Unit has been carried out well and can be said to be effective. This can be seen from 5 indicators, namely goal achievement, work quality, quantity of work, on time, and job satisfaction. This research can be used as a source of information and knowledge about the Work Effectiveness of Employees more in-depth Because in contrast to previous studies that used a lot of quantitative methods that focused on numbers and statistics, this study uses qualitative methods that produce hypotheses and more detailed descriptions of Work Effectiveness in employees, and also see how the development of objects over time. This research also focuses on discussing Effectiveness starting from planning, implementation to evaluation on Employee Work Effectiveness.